Experimental Study on the Effect of Rice Husk Charcoal as an Adsorbent in Bioethanol Purification through Distillation - Suryadi Suryadi; Muhammad Sayuthi; M. Iqbal Adhya Putra; Edy Yusuf; Muhammad Habibi (Electronic Journal of Education, Social Economics and Technology, 2025)
This study investigates the effect of using rice husk charcoal as an adsorbent in adsorption-assisted distillation for bioethanol purification. The research is motivated by the need for more efficient, low-cost, and sustainable bioethanol purification methods, considering the limitations of conventional distillation due to azeotrope formation and high energy consumption. An experimental laboratory method was employed by varying the mass of rice husk charcoal at 3 g, 5 g, and 7 g under a constant operating temperature of 78 °C and an initial ethanol concentration of 70%. Performance parameters analyzed included ethanol concentration improvement, separation efficiency, bioethanol yield, and condenser performance. The results indicate that increasing adsorbent mass significantly enhances ethanol purity, with the highest concentration of 89.4% and maximum separation efficiency achieved at 7 g of adsorbent. However, the highest bioethanol yield was obtained at 3 g of adsorbent, indicating a trade-off between product purity and quantity. Overall, rice husk charcoal is proven to be an effective, environmentally friendly alternative adsorbent with strong potential for application in small- to medium-scale bioethanol purification systems.